Development of an integrated textbook flipbook BUTERI to enhance students’ creative innovation and academic resilience - Ali Yusuf, Furtasan (Indonesian Journal of Educational Development (IJED), 2025)
The increasing demand for innovative and character-strengthening learning media in higher education highlights the urgency of this research. This study aims to develop an integrated textbook flipbook BUTERI capable of enhancing students’ creative innovation and academic resilience. The research method employed is Research and Development, utilizing the 4D model (Define, Design, Development, and Disseminate). The research sample consisted of 60 fifth-semester students from the elementary school teacher education study program, selected through purposive sampling. Data collection techniques included a creative innovation test and non-test techniques such as observation, interviews, academic resilience questionnaires, and documentation. Qualitative data analysis involved data collection, data reduction, data presentation, and conclusion, while quantitative data analysis employed descriptive and inferential statistical analysis. The research findings indicate: (1) Define: Needs analysis revealed the necessity for innovative media to enhance creative innovation and academic resilience; (2) Design: Interactive technology-based media, materials, and evaluations were designed; (3) Development: The media was validated, tested, and proven effective in improving learning outcomes; and (4) Disseminate: The product was disseminated through FGDs and implemented in lectures, and it was proven to enhance creative innovation and academic resilience with positive responses. This study concludes that the integrated textbook flipbook BUTERI can enhance students’ creative innovation and academic resilience.